Efeito do hipoclorito de sódio, EDTA e STERILOX® na microdureza e na estrutura dentinária do canal radicular - Ghisi, Alexandre Corrêa (2014)
The present study aimed to evaluate the influence of the following irrigating solutions on dentin microhardness and structure of the root canal: 2% and 5% NaOCl, 400 ppm Sterilox® and 17% EDTA. Therefore, 80 roots from bovine incisors were randomly divided into 8 groups (n=10): 2% NaOCl, 5% NaOCl, 400 ppm Sterilox®, associated (2NaOCl+E, 5NaOCl+E, Sx+E) or not (2NaOCl, 5NaOCl, Sx) with 17% EDTA (final irrigation for 5 min), 17% EDTA (E), and distilled water (H2O) - negative control. Chemomechanical preparation of the root canals (30 min), using one of the irrigating solutions tested, was performed by the classical technique. All samples were then sectioned perpendicularly to the long axis at the coronal portion in order to obtain a coronal (5 mm) and an apical root segment (15 mm). The thesis was divided into two chapters. First, coronal segments were submitted to Vickers Microhardness Test at two points, one at about 500-1000 μm from the root canal lumen (distance 1) and the other at about 500-1000 μm from the external root surface (distance 2). Wilcoxon test was applied to compare distances 1 and 2 in each group, and Kruskal-Wallis test, followed by Dunn test, compared the groups to each other. The significance level was set at 5%. Results showed microhardness values significantly smaller at distance 1 than distance 2, except for 5NaOCl and 5NaOCl+E (P>0.05). EDTA presented the lowest microhardness values, significantly different only from Sx at distance 2. In conclusion, all tested solutions showed lower microhardness values near the root canal lumen compared to those found near the external root surface, and at this point, EDTA promoted a greater microhardness reduction in comparison to Sterilox®. In the second chapter, apical segments were longitudinally cut into two hemi-roots, one prepared for the study of the collagen structure by light microscopy (LM), and the other for the analysis of the topography of the inorganic component of dentin, by scanning electron microscopy (SEM). Picrosirius stained slides were analyzed and classified into 4 scores classified into four scores according to the orientation pattern of the collagen fibers and the regularity of the root canal contour. SEM images of coronal dentinal tubules near the root canal lumen were analyzed descriptively in relation to their parallelism, obliteration and the presence of dentinal erosion. Data from histological analyzes were submitted to Kruskal-Wallis test followed by multiple comparisons test at 5% significance level. Results showed that the higher the concentration of the NaOCl, the greater its effect, in depth, on organic layer of dentin (collagen). It is possible to conclude that 5% NaOCl, associated or not with 17% EDTA, and 2% NaOCl + EDTA caused the greatest change in the organic matrix of collagen. 2% NaOCl was similar to Sterilox®, associated or not with EDTA, promoting a more superficial disorganization of collagen and in a smaller area. Regarding changes of the inorganic component of dentin, demineralized areas were observed in all groups in which EDTA was employed. However, areas of erosion and open tubules were detected only when it was combined with NaOCl. It was concluded that 5% NaOCl, whether associated or not with 17% EDTA, caused significant damage to dentin collagen. SEM images obtained by SEM revealed demineralization in all groups in which EDTA was used, however areas of erosion and open tubules were observed only when it was combined with NaOCl.